The Study of Tong Composter in Produced Liquid Organic Fertilizer - Aidah Maqbulah Al-Hadi; Yunita Ismail Masjud (Journal of Environmental Engineering and Waste Management, 2021)
Abstract. Inadequate processing of waste in household areas has resulted in many people throwing the waste anywhere. Waste generation can be minimized by using the composting method. There are many methods of composting organic waste; one of them is the Tong Composter. Tong Composter is a composting method which in the process uses an EM4 bio-activator. Objectives: This research objective is to determine whether the liquid organic fertilizer parameters produced comply with the standard of Ministerial Decree of Agriculture No. 261 of 2019. Method and results: This research using the experimental method with two treatments, EM4 dosage (60 ml and 70 ml) and fermentation time (10 days and 20 days). A dose of EM4 in treatment 1 is 60 ml, and treatment 2 is 70 ml; each treatment was analyzed on the 10th day. For treatment 3 and 4, a dose of EM4 in treatment 3 is 60 ml, and in treatment 4 is 70 ml; each treatment was analyzed on the 20th day. Then from the liquid organic fertilizer produced, several parameters were analyzed at PT. Sucofindo Cibitung, such as Nitrogen, P2O5, and K2O parameter. Meanwhile, the pH will be measured in the Environmental Engineering Laboratory of President University. The laboratory experiment results from pH, Nitrogen, P2O5, and K2O will be tested using the t-test. With the hypothesis (HO: µ sample ≥ minimum value of macro-nutrient and pH parameter from Ministerial Decree of Agriculture of the Republic of Indonesia Number 261 of 2019). According to the t-test result, the null hypothesis is rejected because Nitrogen, P2O5, and K2O in all parameters are less than 2%. The null hypothesis is accepted for pH because in all parameters is higher than or equal to 4. Conclusion: The t-test result showed that only the pH was complied with the standard, while the Nitrogen, P2O5, and K2O parameters have not complied with the standard of Ministerial Decree of Agriculture No. 261 of 2019.